Quince años de olimpiadas de matemática en la enseñanza secundaria de Costa Rica (ING) - Adolio, Norma (2003)
In this article we analyze the importance of the Costa Rica Mathematics Olympiads in Secondary Schools in this country. This project has contributed to the development of mathematical, scientific and technological communities in Costa Rica and has caused an international impact through annual tournaments. Also this article describes the achievements and weaknesses of these Olympiads, features of great importance for a deep study of its current state. Based on the knowledge and experience acquired during these fifteen years of Olympiads, it is possible to establish a plan for this project to be developed in years to come.